2017
DOI: 10.1007/s00572-017-0795-7
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal fungi reduce the light compensation point and promote carbon fixation of Pinus thunbergii seedlings to adapt to shade environments

Abstract: We examined the effects of three ectomycorrhizal (ECM) symbionts on the growth and photosynthesis capacity of Japanese black pine (Pinus thunbergii) seedlings and estimated physiological and photosynthetic parameters such as the light compensation point (LCP), biomass, and phosphorus (Pi) concentration of P. thunbergii seedlings. Through this investigation, we documented a new role of ectomycorrhizal (ECM) fungi: enhancement of the survival and competitiveness of P. thunbergii seedlings under low-light conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…In our study, the Chl content was higher in mycorrhizal Q. mongolica seedlings than in control group seedlings under NaCl treatment, and the decrease in the Chl content became less pronounced as the duration of stress increased, indicating that the chloroplasts of the mycorrhizal seedlings were less damaged. This is similar to the change in Chl content observed in the needles of P. thunbergii inoculated with C. geophilum under salt stress [42].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, the Chl content was higher in mycorrhizal Q. mongolica seedlings than in control group seedlings under NaCl treatment, and the decrease in the Chl content became less pronounced as the duration of stress increased, indicating that the chloroplasts of the mycorrhizal seedlings were less damaged. This is similar to the change in Chl content observed in the needles of P. thunbergii inoculated with C. geophilum under salt stress [42].…”
Section: Discussionsupporting
confidence: 86%
“…Under salt stress, plant chloroplasts tend to disintegrate, and the synthesis of chlorophyll and carotenoids is inhibited. Previous studies have shown that ectomycorrhizal fungi can increase the Chl content of P. thunbergii seedlings under salt stress [ 42 ]. In our study, the Chl content was higher in mycorrhizal Q. mongolica seedlings than in control group seedlings under NaCl treatment, and the decrease in the Chl content became less pronounced as the duration of stress increased, indicating that the chloroplasts of the mycorrhizal seedlings were less damaged.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, apple production systems can be considered an important carbon sink in fruit culture (Wu et al, 2012). Similarly, many reports on carbon emission in various crops have been confirmed by other researchers globally (Piao et al, 2009;Bhatnagar et al, 2016;Marín et al, 2016;Shi et al, 2017;Khalsa et al, 2020). Kumar et al (2019) have used various models for estimating biomass of plants, i.e., 225 mg ha −1 with biomass accumulation and carbon storage reduced by roots followed by twigs and leaves and branches.…”
Section: Carbon Capture Of Long Residence Woody Leaf Fruit and Rootsmentioning
confidence: 91%
“…Literature available on carbon fluxes under fruit crop and NPP and GPP for horticultural crops, especially fruit crops (Ceschia et al, 2010;Marín et al, 2016;Shi et al, 2017;Khalsa et al, 2020), is summarized in Table 1. Fruit trees (woody, leaf, fruit, and roots) represent a valuable portion of land use in various areas and have an important role in capturing net carbon dioxide sink and storing carbon compounds in the permanent woody parts of the fruit tree (Scandellari et al, 2016;Chamizo et al, 2017;Tezza et al, 2019).…”
Section: Carbon Capture Of Long Residence Woody Leaf Fruit and Rootsmentioning
confidence: 99%
“…The symbiosis of Pisolithus species with trees promotes the carbon and nutrient cycling of the forest ecosystem ( Cairney et al, 1989 ). In addition, the Pisolithus symbionts can promote the growth of plants, the absorption of mineral elements, and enhance the ability of plants to cope with abiotic stress, including drought, heavy metals and nutritional deficiencies ( Jourand et al, 2014 ; Shi et al, 2017 ; Sebastiana et al, 2018 ). Up to now, more than ten species have been described in the genus Pisolithus .…”
Section: Introductionmentioning
confidence: 99%